(untitled) (Journal of the College of Basic Education, 2022)
The sample of high temperature superconductivity of type Tl-2223 ( Tl2 Ba2Ca2Cu3O10+d ) have been prepared by using solid state reaction method . The samples have been prepared at the sintering temperature (840o C) for (24h ) at average heating rate ( 2o C/ Min ) and hydrostatic pressure (8 ton / cm2). The partial substitution effect of(Ag) in (Tl) and ( Sr ) in ( Ba ) in the compound as (Tl2Ba2-ySryCa2Cu3O10+d ) has been investigated where (x= y= 0.1, 0.2 and 0.3). The X-Ray diffraction patterns were obtained , the compound has been characterized as ( Tl-2223 ) having tetragonal structure with lattice parameters ( a=b=3.91 ) and (c= 33.54 for ( x=y=0 ). Also the X-Ray diffraction data showed that the structure of the compound is tetragonal phase in the rang